2014
DOI: 10.1089/adt.2013.532
|View full text |Cite
|
Sign up to set email alerts
|

The myImageAnalysis Project: A Web-Based Application for High-Content Screening

Abstract: A major challenge faced by screening centers developing image-based assays is the wide range of assays needed compared to the limited resources that are available to effectively analyze and manage them. To overcome this limitation, we have developed the web-based myImageAnalysis (mIA) application, integrated with an open database connectivity compliant database and powered by Pipeline Pilot (PLP) that incorporates dataset tracking, scheduling and archiving, image analysis, and data reporting. For system admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…To visualize directly the population of fluorescing cells, assess the effect of vector length on transfection by a separate method, and test multiple concentrations of vector doses, we used fluorescence microscopy and an automated method [21] to quantify GFP knockdown. We transfected each of the unlabeled vectors at 4, 40, or 400 fmol into HeLa-GFP cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To visualize directly the population of fluorescing cells, assess the effect of vector length on transfection by a separate method, and test multiple concentrations of vector doses, we used fluorescence microscopy and an automated method [21] to quantify GFP knockdown. We transfected each of the unlabeled vectors at 4, 40, or 400 fmol into HeLa-GFP cells.…”
Section: Resultsmentioning
confidence: 99%
“…For each experiment, “no DNA added” and pT7 (a plasmid that encodes the same shRNA as the other vectors, but under a T7 promoter that does not express in mammalian cells), served as negative controls. From high resolution fluorescent images, cell area was calculated and GFP fluorescence per cell was quantified (S1 Fig) [21]. This process was done for the entirety of one visual field per well of a 96-well plate, with the total cells read ranging from 680 to 6,407 (depending on the number of cells visible in each field) for each transfection condition (Fig 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel project, we embarked on a small library screen of FDA approved drugs to establish classes of bioactive molecules inhibiting AR signaling, which may be useful to treat CRPC [18]. Enrichment analysis of active compounds showed that histone deacetylase inhibitors (HDACi) were most active (manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…According to a number of recent reports [10, 11], the accumulation in the recurring tumor of the carboxyl terminal truncated and constitutively active AR variant (AR-V), AR-V7 [12-17] is an important contributor to resistance to second generation ADT. In a parallel project, we embarked on a small library screen of FDA approved drugs to establish classes of bioactive molecules that inhibit AR and AR-V7 signaling, and thus may be useful to treat CRPC [18]. One class of compounds identified with this approach (manuscript in preparation) consisted of histone deacetylase inhibitors (HDACi), which lead to testing commercially available agents with the same mechanism of action.…”
Section: Introductionmentioning
confidence: 99%